MEDITATION, MEDIATED: INTEGRATING TECHNOLOGICAL AFFORDANCES AND THE UTAUT MODEL IN STUDYING DIGITAL MENTAL HEALTH APPLICATIONS - Talekar, Rachana Lalit; Xia, Yiping (AoIR Selected Papers of Internet Research, 2026)
In recent years, the digital delivery of mindfulness-based interventions for anxiety and stress relief has gained popularity among the general population. However, there is a lack of research on how users navigate those specially designed mobile applications(apps) and how their mental health journeys may be shaped by the design processes that constitute their interactions with the app. Given the reach and scale of Headspace app’s user base, there is an opportunity to study the design and user experience. Integrating the concept of technological affordances and the Unified Theory of Acceptance and Use of Technology (UTAUT-2), this study seeks to answer the following research question: How do the characteristics of the Headspace mobile app enable or constrain different aspects of the user’s mental health journey? The findings reveal that Headspace offers affordances such as accessibility, progress tracking, and privacy, which influence user engagement and experience. The affordances notably intersect with UTAUT-2, thereby providing a robust design to understand the sociotechnical dynamics of using digital mental health tools. Overall, this study provides insight into user experience and interpretation of affordances, demonstrating the relationship between design elements and individual perceptions that can iteratively inform digital experience.